Practices, attitudes and motives for domestic waste recycling - Aini, M. S.; Fakhru'l-Razi, A.; Lad, S. M.; Hashim, A. H. (Informa UK Limited, 2002)
Solid household waste management in Malaysia has reached a critical stage. Increasing population, urbanization and changing patterns of lifestyle have instigated the phenomenon. The 15 000 tonnes of garbage produced daily are thrown into 230 landfills nationwide, where 80% of them have only two years of life span left. Although recycling programmes were launched as early as 1990, only 5% of the wastes are recycled. The purpose of the present research was to ascertain the current management of household solid waste, attitude and motivational factors towards recycling. Data were collected using interview survey on 150 households in an urban residential area. The findings demonstrated that the respondents had very low awareness and knowledge regarding local domestic waste management. Separation of organic and non-organic wastes was rarely practised by 76% of the respondents. Most waste was thrown away, except for newspaper and aluminium cans which were regularly recycled, while furniture, and electrical items were reused by giving away or trading-in. The attitude of the respondents towards recycling was modest. Of the five motivational factors, intrinsic satisfaction and individual commitment were more important reasons for recycling than convenience, economic motivation and societal commitment. The results of the study indicated that, in order to overcome the solid waste crisis, the conscience of the individual needs to be raised through environmental awareness and concern, inculcation of sustainable consumption practices and education on waste management.